Characterization of codfish gelatin: A comparative study of fresh and salted skins and different extraction methods. (March 2022) - Alves, Ana Luísa; Fraguas, Francisco Javier; Carvalho, Ana Cristina; Valcárcel, Jesús; Pérez-Martín, Ricardo Isaac; Reis, Rui Luís; Vázquez, José Antonio; Silva, Tiago Henriques
Abstract: The use of alternative sources for gelatin extraction is in demand in today's industries. Fish skins are an economical and sustainable source option. However, there is a lack of information about the preservation state of skins (fresh, frozen, salted, etc.) and how that affects the gelatin yield and properties, and therefore, compromise the final product. In this study we present a comparative analysis between different reported gelatin extraction processes for fresh and salted codfish ( Gadus morhua ) skins. The extracted products were characterized based on yield of extraction, amino acid composition, molecular weight distribution, rheological properties and gel strength, as well as the cell compatibility of the gelatins envisaging future biomedical applications. Results showed that extraction method affected the yield and gelatin properties within the same type of fish skin. Thus, it was found that water acidification step, demonstrated higher extraction yield, while other methods produced gelatins rich in OH-proline + proline, promoting enhanced gel strength and rheological properties. There is thus a compromise between yield and gelatin properties that industries need to understand before selecting their gelatin extraction method. Results, also showed that gelatins derived from salted skins demonstrated lower viscoelastic properties and gel strength, when compared with gelatins from fresh skins. Our research represents a unique comparative compilation of different extraction methods in cod skins differently conserved, as a tool on the quest for the sustainable valorization of fish by-products, included in a circular economy framework. Graphical abstract: Image 1 Highlights: Fish gelatins produced from fresh and salted cod skins using different approaches. Pre-treatments performed at 4 °C enable more efficient extractions. Phosphoric acid and hot water in one step leads to a higher extraction yield. The use of sulphuric and citric acid rendered gelatins with higher gel strength. Gelatins from salted skins showed lower physical properties then gelatins from fresh skins.